SURVIVAL RATE PENYANDANG HIPERTENSI DENGAN KONSUMSI NATRIUM RENDAH TERHADAP KEJADIAN STROKE - Rahajeng, Ekowati; Riyadina, Woro (GIZI INDONESIA, 2016)
Stroke is the leading cause of death and disability in the world. Several studies have shown that stroke can be prevented through modifiable risk factors. The adequate treatment of hypertension may reduce the risk of stroke. Lifestyle modification such as reducing salt intake in hypertension management have demonstrated lowering blood pressure, enhancing the effectiveness of antihypertension drugs and also reducing stroke risk. This study aims to verify the survival rate of hypertension with lower sodium intake (<2000 mg per day) on the incidence of stroke. The study was conducted through a prospective cohort study (4 years of follow-up) in 1082 people with confirmed hypertension. Stroke were confirmed by neurologist. The consumption of sodium, sugar and fat were collected through 24-hour dietary recall. Hypertension survival rate was calculated using Life Table Survival analysis. This study has demonstrated evidence of the higher survival rate of hypertension with low sodium intake on the incidence of stroke, with the difference 2-year survival rate is 3 percent higher and 4-year survival rate is 5 percent higher. Sodium consumption of <2000 mg per day in people with hypertension has prevented a 78 percent incidence of stroke. Therefore, the intervention programs to reduce of the consumption of salt or sodium in Indonesia should be prioritized.